Severe SARS‐CoV‐2 patients develop a higher specific T‐cell response. Issue 12 (23rd December 2020) - Demaret, Julie; Lefèvre, Guillaume; Vuotto, Fanny; Trauet, Jacques; Duhamel, Alain; Labreuche, Julien; Varlet, Pauline; Dendooven, Arnaud; Stabler, Sarah; Gachet, Benoit; Bauer, Jules; Prevost, Brigitte; et al.
Abstract: Objectives: Assessment of the adaptive immune response against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is crucial for studying long‐term immunity and vaccine strategies. We quantified IFNγ‐secreting T cells reactive against the main viral SARS‐CoV‐2 antigens using a standardised enzyme‐linked immunospot assay (ELISpot). Methods: Overlapping peptide pools built from the sequences of M, N and S viral proteins and a mix (MNS) were used as antigens. Using IFNγ T‐CoV‐Spot assay, we assessed T‐cell and antibody responses in mild, moderate and severe SARS‐CoV‐2 patients and in control samples collected before the outbreak. Results: Specific T cells were assessed in 60 consecutive patients (mild, n  = 26; moderate, n  = 10; and severe patients, n  = 24) during their follow‐up (median time from symptom onset [interquartile range]: 36 days [28;53]). T cells against M, N and S peptide pools were detected in n  = 60 (100%), n  = 56 (93.3%), n  = 55 patients (91.7%), respectively. Using the MNS mix, IFNγ T‐CoV‐Spot assay showed a specificity of 96.7% (95% CI, 88.5–99.6%) and a specificity of 90.3% (75.2–98.0%). The frequency of reactive T cells observed with M, S and MNS mix pools correlated with severity and with levels of anti‐S1 and anti‐RBD serum antibodies. Conclusion: IFNγ T‐CoV‐Spot assay is a reliable method to explore specific T cells in large cohorts of patients. This test may become a useful tool to assess the long‐lived memory T‐cell response after vaccination. Our study demonstrates that SARS‐CoV‐2 patients developing a severe disease achieve a higher adaptive immune response. Abstract : We quantified IFNg‐secreting T cells reactive against the M, N and S viral SARS‐CoV‐2 proteins using a standardized enzyme‐linked immunospot assay in 60 patients. The frequency of reactive T cells correlated with severity, and with levels of anti‐S1 and anti‐RBD (receptor binding domain) serum antibodies, demonstrating a higher adaptive immune response after developing a more severe disease. IFNg T‐CoV‐Spot assay may also become a useful tool to assess the long‐lived memory T cell response after vaccination.